Intellectual Capital Disclosure Based Stakeholders Pada Perbankan Indonesia - Enok Nurhayati; Lia Uzliawati (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
This study analyses Indonesia stekholders viewpoints on Intellectual Capital Disclosure items using Intellectual Capital Disclosure Index. Respodents on this research is narrow financial based stakeholders. Respondents rating showed high average scores of 5,88 with all items. These score indicated that there is clear expectation of stakeholders for Indonesian banking sector to disclosed all of items. The weighted Indonesia Intellectual Capital Disclosure Index on Bankingis developed based on insight of survey responden which better reflect the importance of key stakeholders demand for Intellectual capital disclosure in Indonesia Banking Sector.